Reflow of tiny 01005 capacitor/SAC305 solder joints in protective atmosphere. Issue 3 (5th June 2017) - Tao, Yeqing; Ding, Dongyan; Li, Ting; Guo, Jason; Fan, Guoliang
Abstract : Purpose: This paper aims to study the influence of reflow atmosphere and placement accuracy on the solderability of 01005 capacitor/SAC305 solder joints. Design/methodology/approach: The 01005 capacitors were mounted on OSP-coated pads, and the samples were fabricated in four different atmospheres, i.e. 200 ppm O2 /N2, 1, 000 ppm O2 /N2, 3, 000 ppm O2 /N2 and air. After the reflow process, visual inspection and X-ray detection were carried out to examine the solder joint shapes and possible defects. Some of the samples fabricated in different conditions were cross-sectioned and the solder joint microstructures were analyzed. On the other hand, besides placing the components on their normal pad positions, a 50 per cent offset of the x -axis (long axis) or y -axis (short axis) was introduced into the chip mounter programs to evaluate the 01005 capacitor's assembly sensitivity to placement accuracy. The process-induced defects were investigated. Findings: Experimental results indicated that an N2 -based protective atmosphere was necessary for 01005 type assembly, as it could obviously improve the 01005 solder joint quality, compared with the air condition. The protective atmosphere had little effect on the appearance, quality and microstructure of solder joints when the oxygen concentration was below 3, 000 ppm. But a very low oxygen concentration could increase the risk of tombstoning defects for the assembly process. The N2 -based protective atmosphere containing 1, 000-2000 ppm O2 was acceptable and appropriate for the assembly of tiny components. Originality/value: The results of this work provide a set of reflow process parameters and recommendations for 01005 size component assembly in manufacturing.